STRATEGI KOMUNIKASI DAKWAH AN-NADZIR MELALUI KAJIAN PROFETIK - Ibnu Azka (Jurnal Dakwah Tabligh, 2022)
Carrying out da'wah activities is an obligation for every Muslim, the da'wah movement as an agent of social change will be faced with various problems in accordance with the demands of the present era. Along with the development of human civilization that is increasingly advanced and civilized. This paper explores the da'wah movement with An-Nadzir da'wah communication strategy with the Kuntowijoyo prophetic social studies approach. The results of this analysis indicate that the communication strategy applied by an-Nadzir has prophetic principles, namely humanization, liberation, and transcendence so that the da'wah is effective and creates a stable community.